If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + -86 = 3c + -14 Reorder the terms: -86 + 6c = 3c + -14 Reorder the terms: -86 + 6c = -14 + 3c Solving -86 + 6c = -14 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. -86 + 6c + -3c = -14 + 3c + -3c Combine like terms: 6c + -3c = 3c -86 + 3c = -14 + 3c + -3c Combine like terms: 3c + -3c = 0 -86 + 3c = -14 + 0 -86 + 3c = -14 Add '86' to each side of the equation. -86 + 86 + 3c = -14 + 86 Combine like terms: -86 + 86 = 0 0 + 3c = -14 + 86 3c = -14 + 86 Combine like terms: -14 + 86 = 72 3c = 72 Divide each side by '3'. c = 24 Simplifying c = 24
| 3x+18=6x-9 | | 6x+6=-38-5x | | 3ab+7b= | | 7+6x=-18+x | | 6x^2+6y^2=144 | | 7+6x=-18x+x | | 13-3x=5-2x | | -4x+14=54 | | 9h+10h+7h-6h-16h=10 | | 6(x+2)=6x+14 | | 4(x+6)+3=-3 | | 11r^2-15r=-4 | | 5+65c=39c+13 | | 17j-16j-j+j=16 | | 6k-4k-k=12 | | 6k+5k+16k+4k=15 | | 6c+c+2c=9 | | -8+2c=-32+11c | | 26=3b-2-1b | | cosx=10x | | 2c-5c=14 | | 10g-5g+4g-2g-2g=20 | | 2x(3x+5)+5=8 | | 4c+9=-57-7c | | 20m+5m-21m-2m=14 | | 3(x+4)-7=29 | | 2x+11=-3x-18 | | lnx=3.5 | | 2x+11=2x-18 | | (-13r)+r-8r=12 | | 18-6c=8-7c | | 4g-g-2g=10 |